2019
DOI: 10.1371/journal.pone.0208246
|View full text |Cite
|
Sign up to set email alerts
|

Oral health status of the disabled compared with that of the non-disabled in Korea: A propensity score matching analysis

Abstract: BackgroundThere are many types of disabilities, and each type has a variety related to socioeconomic factors. Such factors affect to many health problems of the disabled. However, surveys of the oral health status of the disabled in Korea are rare.ObjectiveThe purpose of this study was to estimate oral health disparity through comparing oral health status of the disabled to the non-disabled, adjusted for the net effect of the disability on oral health status.MethodsA cross-sectional study was conducted among t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 18 publications
3
41
0
1
Order By: Relevance
“…As a matter of fact, it is expected to see a lower hygiene status among individuals with multiple disabilities, particularly those with conditions causing cognitive and psychomotor impairment. Previous authors reported that there is a correlation between the level of oral hygiene and the degree of disability [26]. Obviously, this group of subjects needs extra attention and probably the efforts of the caregivers at home are insufficient to provide efficient oral care.…”
Section: Discussionmentioning
confidence: 99%
“…As a matter of fact, it is expected to see a lower hygiene status among individuals with multiple disabilities, particularly those with conditions causing cognitive and psychomotor impairment. Previous authors reported that there is a correlation between the level of oral hygiene and the degree of disability [26]. Obviously, this group of subjects needs extra attention and probably the efforts of the caregivers at home are insufficient to provide efficient oral care.…”
Section: Discussionmentioning
confidence: 99%
“…These differences may vary according to the country and the types of disabilities included in the survey. In South Korea, researchers evaluated comparable samples of people (a) with physical disabilities (DMFT = 7.3), (b) with mental disabilities (DMFT = 8.3), and (c) with multiple disabilities (DMFT = 8.2) and people without disabilities (DMFT = 4.9) [ 6 ]. In another study carried out in Portugal, with institutionalized people with disabilities, a mean DMFT of 11.2 was found which was much higher than the general population of the same age group [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“… People with disabilities are often unable to maintain oral hygiene, and have relatively more oral disease and traumatic dental injuries. 6 They often need immediate emergency dental treatment due to severe pain. People with disabilities may be unable to maintain personal hygiene and often have additional systemic diseases that make them relatively more vulnerable to COVID-19.…”
Section: Additional Considerations For Patients With Special Needsmentioning
confidence: 99%
“…People with disabilities are often unable to maintain oral hygiene, and have relatively more oral disease and traumatic dental injuries. 6 They often need immediate emergency dental treatment due to severe pain.…”
Section: Additional Considerations For Patients With Special Needsmentioning
confidence: 99%